Intention to Adopt Meta Collaborative Performance Advertising Tool Known as Collaborative Ads by SMEs in Indonesia - Kalani, Jonah Royleri (Electronic Journal of Business and Management, 2024)
The research aims to examine the behavioral intention of SMEs in Indonesia to adopt a meta collaborative performance advertising solution called Collaborative Ads. Currently, the issues and concerns faced by SMEs include a lack of awareness and concern for cost and support. There is a dearth of studies that examined the antecedents that can influence the adoption of Collaborative Ads. The study was based on the Technology Acceptance Model (TAM). The predictors of intention to adopt collaborative ads were IT Infrastructure, Relative Advantage, Return on Investment (ROI), and Top Management Support. In this quantitative study, a survey strategy using self-administered was used. By using convenience sampling, 133 responses from SMEs in Indonesia. The analysis done using SPSS showed good reliability. The multiple regression analysis revealed that IT infrastructure had the highest impact on the intention to adopt Collaborative Ads. The other three predictors were not supported. This study highlights the importance of IT Infrastructure and SMEs should invest in IT Infrastructure to reap the benefits of Collaborative Ads. To the knowledge of the researcher, this study is the first of its kind done among SMEs in Indonesia. The study highlighted the critical role of IT Infrastructure.